Arterial thrombosis and accelerated atheroma in a member of a family with familial antithrombin III deficiency. Issue 676 (February 1982) - Winter, J.; Bennett, B.; Donald, D.; Douglas, A. S.
Abstract : The case is described of a young man with probable familial antithrombin III deficiency, a disorder associated with a marked predisposition to venous thrombo-embolic events. In addition to a history of venous thrombosis and pulmonary embolism, at post-mortem this patient demonstrated widespread arterial thrombosis and atheroma. The probable association of severe arterial thrombosis and atheroma with a clearly definable coagulation disorder predisposing to thrombosis is of interest.